2013
DOI: 10.1177/0973174113504848
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital in Risk-Sharing

Abstract: This article evaluates the role of social capital as a risk-coping device in India's Andhra Pradesh state. Focusing on children's nutritional outcomes, we test whether social capital serves as an informal insurance mechanism and helps households minimize the negative effect of shocks. We examine the impact of two kinds of income shocks, idiosyncratic and covariant, and the potentially risk-mitigating role of two types of social capital, structural and cognitive, measured first at the individual and second at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In addition, traditional values and religious beliefs underpin these practices, placing a strong cultural obligation and sanctions on community members to promote cooperation and collective action, build solidarity, and support vulnerable households to cope with shocks. Several studies [12][13][14][15][16] acknowledge the promotive and protective functions of informal mutual support arrangements: before or ex ante, during, and after crisis or ex post situations or shocks. Communities forming such arrangements tend to exhibit better recovery from shocks [16] and need public emergency assistance less urgently than those communities without such arrangements [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, traditional values and religious beliefs underpin these practices, placing a strong cultural obligation and sanctions on community members to promote cooperation and collective action, build solidarity, and support vulnerable households to cope with shocks. Several studies [12][13][14][15][16] acknowledge the promotive and protective functions of informal mutual support arrangements: before or ex ante, during, and after crisis or ex post situations or shocks. Communities forming such arrangements tend to exhibit better recovery from shocks [16] and need public emergency assistance less urgently than those communities without such arrangements [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [12][13][14][15][16] acknowledge the promotive and protective functions of informal mutual support arrangements: before or ex ante, during, and after crisis or ex post situations or shocks. Communities forming such arrangements tend to exhibit better recovery from shocks [16] and need public emergency assistance less urgently than those communities without such arrangements [17]. Nonetheless, studies on resilience, disaster management policy, and practices have yet to fully embrace indigenous mutual support arrangements as a vital component in addressing vulnerability [18][19][20][21][22] against livelihood shocks.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of population affected by disaster was chosen as an instrument for communal economic inequality because when larger numbers of households in a community are affected by disasters, inequality is likely to be higher given the ability of more affluent households to better cushion the disasters’ negative economic impact—on both consumption and wealth—with existing assets. Empirical support for the relationship can be found in studies such as Petrikova and Chadha ( 2013 ) and Howell and Elliott ( 2018 ). The instrumental variable is based on an estimate of the proportion of households within a community affected by natural disaster in the four years prior to the survey, made by 3–4 community representatives in each village and averaged.…”
mentioning
confidence: 83%
“…5 Regardless, social networks, particularly women’s associations, have played an important political role in the state (Niranjana 2002 ). Several empirical studies have also found positive links between social capital and desirable development outcomes in Andhra Pradesh (Galab et al 2006 ; Moestue et al 2007 ; Petrikova and Chadha 2013 ). Investigating how changing levels of community-level inequality in the state affect households’ social capital is thus policy-relevant beyond its theoretical contribution.…”
Section: Contextualising Inequality and Social Capital To India With A Focus On Andhra Pradeshmentioning
confidence: 99%
See 1 more Smart Citation